PD-1/PD-L1 combined with LAG3 is associated with clinical activity of immune checkpoint inhibitors in metastatic primary pulmonary lymphoepithelioma-like carcinoma - Zhong, Yu-Min; Yin, Kai; Chen, Yu; Xie, Zhi; Lv, Zhi-Yi; Yang, Jin-Ji; Yang, Xue-Ning; Zhou, Qing; Wang, Bin-Chao; Zhong, Wen-Zhao; Gao, Ling-Ling; Zhou, Wen-Bin; et al. (Frontiers in Immunology, 2022)
Primary pulmonary lymphoepithelioma-like carcinoma (PLELC) is an Epstein–Barr virus (EBV)-related, rare subtype of non-small-cell lung cancer (NSCLC). Immune checkpoint inhibitors (ICI) show durable responses in advanced NSCLC. However, their effects and predictive biomarkers in PLELC remain poorly understood. We retrospectively analyzed the data of 48 metastatic PLELC patients treated with ICI. Pretreated paraffin-embedded specimens (n = 19) were stained for PD-1, PD-L1, LAG3, TIM3, CD3, CD4, CD8, CD68, FOXP3, and cytokeratin (CK) by multiple immunohistochemistry (mIHC). Next-generation sequencing was performed for 33 PLELC samples. Among patients treated with ICI monotherapy (n = 30), the objective response rate (ORR), disease control rate (DCR), median progression-free survival (mPFS), and overall survival (mOS) were 13.3%, 80.0%, 7.7 months, and 24.9 months, respectively. Patients with PD-L1 ≥1% showed a longer PFS (8.4 vs. 2.1 months, p = 0.015) relative to those with PD-L1 <1%. Among patients treated with ICI combination therapy (n = 18), ORR, DCR, mPFS, and mOS were 27.8%, 100.0%, 10.1 months, and 19.7 months, respectively. Patients with PD-L1 ≥1% showed a significantly superior OS than those with PD-L1 <1% (NA versus 11.7 months, p = 0.001). Among the 19 mIHC patients, those with high PD-1/PD-L1 and LAG3 expression showed a longer PFS (19.0 vs. 3.9 months, p = 0.003). ICI also showed promising efficacy for treating metastatic PLELC. PD-L1 may be both predictive of ICI treatment efficacy and prognostic for survival in PLELC. PD-1/PD-L1 combined with LAG3 may serve as a predictor of ICI treatment effectiveness in PLELC. Larger and prospective trials are warranted to validate both ICI activity and predictive biomarkers in PLELC. This study was partly presented as a poster at the IASLC 20th World Conference on Lung Cancer 2019, 7–10 September 2019, Barcelona, Spain.